A re-consideration of Money Demand Theory - Basant Kapur (German Economic Review (GER), 2025)
Portfolio models typically ignore precautionary transactions demands for liquid assets, and models of precautionary demands typically ignore asset rate-of-return risk. If asset-holders are risk-averse, however, both transactions risk and rate-of-return risk affect demands for both liquid and illiquid assets, even when the two risks are independent of each other. We demonstrate this in a four-asset framework, and show that our integrated treatment produces unexpected and instructive results and insights. For example, (a) an increase in the expected return to risky securities increases the demand for M1, even when M1 is used entirely for transactions purposes, (b) an increase in the variance of securities returns reduces the demand for M1, and (c) an increase in the asset-holders' wealth reduces her demand for M1. A broader framework for the study of money demand is thus called for.
Keywords: E4; G1; G2; 330; asset demands; expected utility; money demand; non-separability